Upstream domains of the Xenopus laevis rDNA promoter are revealed in microinjected oocytes. - Windle, J (1986)
The DNA sequences involved in promoting transcription of the Xenopus laevis rRNA genes were determined by microinjecting a series of deletion mutants into oocyte nuclei. A very small promoter region is sufficient to direct efficient transcription when templates are microinjected at high rDNA concentration, since 5'delta- 9 and 3'delta +6 templates are fully active. However, as the concentration of injected template is decreased, an increasing requirement for upstream domains, extending to nucleotide approximately -170, is observed. The major downstream border of the required region does not change. This apparently expanding 5' promoter border results from the fact that, as the rDNA concentration is decreased, transcription from templates lacking the upstream promoter domain falls off much more sharply than does transcription from a complete promoter. In fact, the deleted promoters are virtually inactive below a threshold rDNA concentration. It is indeed the rDNA concentration that is important, for coinjected vector DNA does not increase the level of transcription obtained from low concentrations of the 5' deletions. From these data we conclude that polymerase I transcription factors can recognize and initiate transcription from a small core promoter domain, but that sequences extending upstream to nucleotide approximately -170 increase the efficiency of initiation. A model is presented that could account for these results.